Multiple functions of the ALT favorite helicase, BLM - Shun Chang; Jiang Tan; Ren Bao; Yanduo Zhang; Jinkai Tong; Tongxin Jia; Jing Liu; Juhua Dan; Shuting Jia (Cell & Bioscience, 2025)
Abstract Eukaryotic somatic cells undergo continuous telomere shortening because of end-replication problems. Approximately 10%~15% of human cancers rely on alternative lengthening of telomeres (ALT) to overcome telomere shortening. ALT cells are characterized by persistent telomere DNA replication stress and rely on recombination-based DNA repair pathways for telomere elongation. The Bloom syndrome (BLM) helicase is a member of the RecQ family, which has been implicated as a key regulator of the ALT mechanism as it is required for either telomere length maintenance or telomere clustering in ALT-associated promyelocytic leukemia bodies (APBs). Here, we summarize recent evidence detailing the role of BLM in the activation and maintenance of ALT. We propose that the role of BLM-dependent recombination and its interacting proteins remains a crucial question for future research in dissecting the molecular mechanisms of ALT.